2012
DOI: 10.1097/cji.0b013e318261e679
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cyclophosphamide, Rituximab, and Intratumoral CpG Oligodeoxynucleotide Successfully Eradicates Established B cell Lymphoma

Abstract: Rituximab plus chemotherapy is standard therapy for patients with non-Hodgkin B cell lymphoma, but often complete response or cure is not achieved. Toll-like receptor 9 agonist CpG oligodeoxynucleotides (CpG) can improve antibody-dependent cellular cytotoxicity and adaptive antitumor immune responses. Using a syngeneic murine B cell lymphoma expressing human CD20 (38C13-huCD20), we previously demonstrated that rituximab plus intratumoral CpG, but not systemic CpG, could eradicate up to half of 7-day establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…26 Whereas the antitumor efficacy of rituximab has previously been enhanced by intra-tumoral administration of the TLR9 agonist CpG, systemic administration of CpG was not effective and as a result only local tumor control secondary to local administration was seen. 27, 28 In this model, NK cells were again shown to be the major effector cell with no apparent role for T cells or macrophages: no loss of therapy was seen in clodronate-liposome-treated mice. However, when a CpG oligonucleotide 1018 ISS was combined with rituximab subcutaneously in a phase II clinical trial the response rate was similar to that reported for rituximab alone.…”
Section: Discussionmentioning
confidence: 83%
“…26 Whereas the antitumor efficacy of rituximab has previously been enhanced by intra-tumoral administration of the TLR9 agonist CpG, systemic administration of CpG was not effective and as a result only local tumor control secondary to local administration was seen. 27, 28 In this model, NK cells were again shown to be the major effector cell with no apparent role for T cells or macrophages: no loss of therapy was seen in clodronate-liposome-treated mice. However, when a CpG oligonucleotide 1018 ISS was combined with rituximab subcutaneously in a phase II clinical trial the response rate was similar to that reported for rituximab alone.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, rituximab plus intratumoral CpG ODNs, but not systemic CpG ODNs, eradicate up to half of 7-day established 38C13-huCD20 tumors, a syngeneic murine B cell lymphoma expressing human CD20. Additionally, brief and extended-duration administration of CpG 7909 in combination with rituximab has been found to be safe in patients with relapsed/refractory non-Hodgkin lymphoma [ 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…42,48,49,[73][74][75][76] Additional methods of enhancing the intratumoral gene therapy have been previously performed with the addition of radiotherapy, chemotherapy, thermal ablation, sorafenib, imatinib, use of ultrasound system, rituximab and dendritic cells to gene therapy administration alone. 34,[77][78][79][80][81][82] In our current study, we used the novel non-viral vector DDMC as the vehicle for the local intratumoral administration of pSicop53. The DDMC was synthesized by graft polymerization of methyl methacrylate (MMA) onto 2-Diethylaminoethyl-Dextran Methyl Methacrylate Copolymer (DAEX).…”
Section: Resultsmentioning
confidence: 99%